2017
DOI: 10.3390/bs7030049
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ethnic and Mainstream Cultures on African Americans’ Health Behaviors: A Qualitative Study

Abstract: Background: Culture plays an important role in shaping individuals’ health behaviors. This qualitative research examines the relationship between African Americans’ ethnic and mainstream cultures and their health behaviors (i.e., food intake and physical activity). Methods: This study used in-depth semi-structured interview format with a group of 25 African Americans to examine the influence of ethnic and mainstream culture on African Americans’ food intake and physical activity. Thematic analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 48 publications
(99 reference statements)
2
18
0
Order By: Relevance
“…Consistent with previous research, a study conducted in New York City reported that affordability, access to healthy food, health knowledge, and personal factors are important in determining healthy behaviors in AAs [47]. Participants often mentioned resilience, reliance on spirituality, dance, music, and social support as important health-enhancing factors endorsed in their AA community [47]. Among Hispanic adults, the absence of reliable access to a sufficient quantity of nutritious food was associated with more rapid cognitive decline [48].…”
Section: The Sociocultural Context Of Eating and Food Selectionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous research, a study conducted in New York City reported that affordability, access to healthy food, health knowledge, and personal factors are important in determining healthy behaviors in AAs [47]. Participants often mentioned resilience, reliance on spirituality, dance, music, and social support as important health-enhancing factors endorsed in their AA community [47]. Among Hispanic adults, the absence of reliable access to a sufficient quantity of nutritious food was associated with more rapid cognitive decline [48].…”
Section: The Sociocultural Context Of Eating and Food Selectionsupporting
confidence: 81%
“…Although providers were constantly involved in patient education, participants reported receiving this information from other sources [45,46]. Consistent with previous research, a study conducted in New York City reported that affordability, access to healthy food, health knowledge, and personal factors are important in determining healthy behaviors in AAs [47]. Participants often mentioned resilience, reliance on spirituality, dance, music, and social support as important health-enhancing factors endorsed in their AA community [47].…”
Section: The Sociocultural Context Of Eating and Food Selectionsupporting
confidence: 60%
“…Cultural differences have a substantial effect on lifestyle. Studies have shown the importance of addressing issues related to health beliefs and practices of culturally diverse groups [42,43]. Our path model supported eight determinants (age, gender, education, chronic illness, family history of ischemic heart disease, health care facility distance, health literacy and metabolic syndrome knowledge) for healthy lifestyle practice against metabolic syndrome.…”
Section: Discussionmentioning
confidence: 55%
“…Several possible reasons might be responsible for this discrepancy. First, some African Americans may perceive healthy eating as not being aligned with their cultural heritage [76,77]. The emphasis on soul food in African American culture might make engaging in a healthy diet difficult, as these foods are often high in fat and calorie density [68].…”
Section: Discussionmentioning
confidence: 99%